Radikalisme, Liberalisme, dan Tantangan Keberlanjutan Aswaja di Era Transformasi Global - Syaifudin Zuhri; Fitroturohmawati Fitroturohmawati; Jihan Nur Millasari; Faridah Faridah; Saifuddin Saifuddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The era of global transformation, marked by the rapid advancement of information technology, the globalization of thought, and the openness of religious discourse, has brought serious implications for the sustainability of Ahlussunnah wal Jama’ah (Aswaja). On the one hand, religious radicalism develops through rigid and exclusive textual interpretations; on the other hand, religious liberalism emerges through approaches that tend to be relativistic and deconstructive toward Islamic teachings. Both currents pose ideological challenges to the existence of Aswaja as a moderate Islamic manhaj. This article aims to analyze the forms of challenges posed by radicalism and liberalism to the sustainability of Aswaja in the era of global transformation and to reaffirm the relevance of Aswaja values in maintaining religious balance. This study employs a qualitative approach, utilizing a library research method to analyze classical and contemporary literature related to Aswaja, radicalism, and liberalism. The findings indicate that Aswaja principles such as tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i‘tidal (justice) play a strategic role in responding to global challenges and sustaining moderate Islam. Therefore, strengthening the internalization of Aswaja values is an urgent necessity in addressing the dynamics of contemporary Islamic thought.   Keywords: Aswaja, Radicalism, Liberalism, Global Transformation, Moderate Islam